Crystallographic structure and energetics of the Rh(1 0 0)-(3 × 1)-2O phase. (7th August 2017) - Kißlinger, T; Ferstl, P; Schneider, M A; Hammer, L
Abstract: In this study we investigate the crystallographic structure of the Rh(1 0 0)-( 3 × 1 )-2O phase by quantitative low energy electron diffraction (LEED) and scanning tunnelling microscopy as well as the energetics of the system applying density functional theory calculations (DFT). The ( 3 × 1 ) structure forms upon exposing the clean Rh(1 0 0) surface to 1200 L of oxygen at 520 K. A full-dynamical LEED intensity analysis (Pendry R-factor R = 0.095 ) reveals an oxygen-induced shifted row-reconstruction of the rhodium top layer where every third Rh-row is displaced by half a surface lattice parameter along the [0 1 1]-direction. There are two oxygen atoms within the unit cell which assume threefold coordinated sites on both sides of the shifted Rh-row with one bond to the shifted and two bonds to the unshifted rows. DFT calculations yield a total energy gain of 0.27 eV per oxygen atom compared to adsorption on the unreconstructed surface. This by far overcompensates the energetic penalty of 0.10 eV per oxygen atom for shifting the Rh-row and thus drives the substrate reconstruction. A coadsorption of oxygen at remaining regular sites of the substrate is not observed in experiment and is found to be energetically unfavorable.